The Influence of Waste Perlite Powder on Selected Mechanical Properties of Polymer–Cement Composites - Beata Jaworska; Dominika Stańczak; Paweł Łukowski (Buildings, 2024)
The subject of this paper is the influence of the partial substitution of cement with mineral additive on the properties of polymer–cement composites (PCCs). Although there is considerable research on the use of perlite in cement concrete, most of the previous studies were conducted with expanded perlite or ground waste perlite, and there is a lack of results evaluating its suitability with polymer–cement composites. To fill this gap, this paper presents the mechanical characteristic of PCC mortars containing waste perlite powder. The modification consisted of replacing part of the cement with waste perlite powder, a byproduct formed during the expansion and fractionation of perlite. The granulometric characteristics of the powder were compiled, and its specific surface area and density were determined. A chemical composition analysis was also carried out. An aqueous dispersion of styrene–acrylic copolymer was used as a polymer modifier. The proportions (by mass) between the contents of the PCC composite components, i.e., cement/polymer (0 to 20%) and cement/mineral powder (0 to 15%), were used as material variables. The technical characteristics tested included the compressive, flexural, and tensile strengths at 28 and 90 days of curing. The compositions of the tested composites were determined using the statistical planning of the experiment. At a low polymer-modifier content in PCC mortars (2.93%), the tested mechanical strengths decreased by five times, with a 6-fold increase in waste content. For mortars containing more than 10% of the polymer modifier, no effect of waste material powder on the flexural strength was observed, while with relatively minor reductions in compressive strength of 2% and 5% and tensile strength of 4% and 2% were observed after 28 and 90 days of curing, respectively. It was shown that it is possible to use waste perlite powder as an ingredient in construction polymer–cement composites, while there is a limiting waste content, above which there is a deterioration in mechanical properties.